Effectiveness of IV cannulation skills laboratory training and its transfer into clinical practice: a randomized, controlled trial. - Frederike Lund; Jobst-Hendrik Schultz; Imad Maatouk; Markus Krautter; Andreas Möltner; Anne Werner; Peter Weyrich; Jana Jünger; Christoph Nikendei (PLoS ONE, 2012)
BACKGROUND: The effectiveness of skills laboratory training is widely recognized. Yet, the transfer of procedural skills acquired in skills laboratories into clinical practice has rarely been investigated. We conducted a prospective, randomised, double-blind, controlled trial to evaluate, if students having trained intravenous (IV) cannulation in a skills laboratory are rated as more professional regarding technical and communication skills compared to students who underwent bedside teaching when assessed objectively by independent video assessors and subjectively by patients. METHODOLOGY AND PRINCIPAL FINDINGS: 84 volunteer first-year medical students were randomly assigned to one of two groups. Three drop-outs occurred. The intervention group (IG; n = 41) trained IV cannulation in a skills laboratory receiving instruction after Peyton's 'Four-Step Approach'. The control group (CG; n = 40) received a bedside teaching session with volunteer students acting as patients. Afterwards, performance of IV cannulation of both groups in a clinical setting with students acting as patients was video-recorded. Two independent, blinded video assessors scored students' performance using binary checklists (BC) and the Integrated Procedural Protocol Instrument (IPPI). Patients assessed students' performance with the Communication Assessment Tool (CAT) and a modified IPPI. IG required significantly shorter time needed for the performance on a patient (IG: 595.4 SD(188.1)s; CG: 692.7 SD(247.8)s; 95%CI 23.5 s to 45.1 s; p = 0.049) and completed significantly more single steps of the procedure correctly (IG: 64% SD(14) for BC items; CG: 53% SD(18); 95%CI 10.25% to 11.75%; p = 0.004). IG also scored significantly better on IPPI ratings (median: IG: 3.1; CG: 3.6; p = 0.015;). Rated by patients, students' performance and patient-physician communication did not significantly differ between groups. CONCLUSIONS: Transfer of IV cannulation-related skills acquired in a skills laboratory is superior to bedside teaching when rated by independent video raters by means of IPPI and BC. It enables students to perform IV cannulation more professionally on volunteer students acting as patients.